2013
DOI: 10.1016/j.jpainsymman.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

A Home-Based Exercise Program to Improve Function, Fatigue, and Sleep Quality in Patients With Stage IV Lung and Colorectal Cancer: A Randomized Controlled Trial

Abstract: Context Exercise benefits patients with cancer, but studies of home-based approaches, particularly among those with Stage IV disease, remain small and exploratory. Objectives To conduct an adequately powered trial of a home-based exercise intervention that can be facilely integrated into established delivery and reimbursement structures. Methods Sixty-six adults with Stage IV lung or colorectal cancer were randomized, in an eight-week trial, to usual care or incremental walking and home-based strength trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
326
0
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(345 citation statements)
references
References 37 publications
6
326
0
13
Order By: Relevance
“…Interventions involving physical activity (44,45) and systematic self-monitoring of physical symptoms (46) should be included in a fatigue-pain management pathway for advanced cancer…”
Section: Discussionmentioning
confidence: 99%
“…Interventions involving physical activity (44,45) and systematic self-monitoring of physical symptoms (46) should be included in a fatigue-pain management pathway for advanced cancer…”
Section: Discussionmentioning
confidence: 99%
“…Inkább több alkalommal, kisebb intenzitással és kevesebb ideig alkalmazzunk gyógytornát [27]! A beteg életkora, testsúlya, egyéb betegségei, szociális és családi háttere is befolyásolhatják a gyógytorna típu-sát.…”
Section: Paramétereiunclassified
“…Ki-emelten fontos aktív tumoros betegeknél stabilizációs gyógytorna alkalmazása, amely révén a fájdalmas ízület-vagy gerincszegmentum terhelése mérsékelhető, ezáltal a fájdalom enyhíthető. Az izomerő növelésével pedig a beteg önellátása könnyebbé válik [4,27].…”
Section: Stabilizáció éS Tehermentesítésunclassified
“…In the series by Morris and co-workers [44], not only solid tumors (among them not only NSCLC) but also hematological malignancies are included; the Authors concluded that an aerobic exercise program determined significant improvements in exercise tolerance; moreover, in a randomized clinical trial carried out by Cheville [45], patients with advanced stages of lung cancer and colorectal cancer were enrolled and underwent home training regimens: results showed improvements in exercise tolerance and quality of life, although very often worsening of the disease can lead to a high dropout rate [46]; finally a recent meta-analysis performed by Jones et al [47], examined six randomized trials within a controlled group (a total 571 patients with breast or prostate cancers or lymphomas), and found that anaerobic training programs may produce a significant increase in VO 2 peak, without any major adverse events. Based on these studies, our opinion is that when feasible, a structured program of aerobic exercise training should always be offered to patients with lung cancer, as a safe and effective method in improving physical performance and quality of life; therefore, it should become part of the overall management of these patients with the same relevance given to the symptoms and pain control.…”
Section: Rehabilitation In Patients With Advanced Cancer (Palliative mentioning
confidence: 99%